Pengaruh Penerapan E-Filling dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pare Kediri - Azhimatul Fikri Izzati; Dwi Ari Pertiwi (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
The purpose of this study is to determine the effect of the application of E-filling and awareness of taxpayers on the compliance of individual taxpayers in KPP Pratam Pare Kediri This study uses quantitative methods with a population of 48,114 taxpayers and 397 samples of taxpayers using the formula slovin. The result of this research is partial influence on the application of e-filling on compliance of individual taxpayer. This negative influence shows that the higher the cash turnover, the value of profitability will decrease. Inventory turnover has no effect on profitability. Then simultaneously the cash turnover and inventory turnover have an effect onprofitabiliti.